(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with issues related to the standardization of the field of medical informatics. Basic definitions, an overview of specific standards are given, and promising directions of development in this area are outlined. Almost all existing standards of medical informatics.